A Compact Isolated CR Antenna System for Application in C-Band - Rajeev K. Parida; Abdulkarem H. M. Almawgani; Arjuna Muduli; Dhruba C. Panda; Adam R. H. Alhawari; Amrindra Pal; M. M. Abdullah; Hasan B. Albargi (International Journal of Antennas and Propagation)
In this work, a dual-port antenna system is simulated and fabricated for cognitive radio (CR) application. The proposed system comprises a tapered-fed monopole ultra-wideband (UWB) sensing antenna and a dual-narrowband (NB) communicating antenna. For miniaturization, the UWB sensing antenna is placed on the front side of the communicating antenna. The sensing operation takes place over 2.1–12 GHz. The E-shaped dual-band antenna operates at 3.9 GHz and 6.04 GHz. The envelope correlation coefficient (ECC) and isolation are measured to be lower than 0.12 and greater than 18 dB, respectively, within the range of acceptable values for both parameters. The antenna prototype was fabricated and tested experimentally to confirm the simulation’s findings. The outcomes of both the simulation and the testing revealed a definite consistency. This work gives a miniaturized model and good isolation, which is appropriate for C-band applications.